التمكين في ضوء القرآن الكريم : دراسة تحليلية لنماذج مختارة - داوود، مريم (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2019)
This research studies the topic of empowerment in the Holy Quran which is one of the key concepts in the Qur'anic in relation to Man's covenant with The Creator. It is important to emphasize that the Quran has dealt with the issue of empowerment in all of its aspects, which confirms its vital role in the present of the Ummah. The Holy Quran designs the nature of this concept, its conditions, its objectives, and its different levels. It also addresses its theoretical dimension and some of the practical aspects related to it through presentation of the forms of empowerment in some prophetic experiments in order to establish the foundations of truth in the present of human being and to build civilization awareness that will elevate the Ummah to achieve the supreme objective of worship. The research will be carried out through the adoption of the inductive method to monitor the reality of this concept, and track the resources, uses, and indications in the Quran. The adoption of analytical method is to explain its reality, conditions, aims and objectives, and to demonstrate it in some of the prophetic experiences. Hence, an analysis of the concept of empowerment in the view of Sayyid Qulb, and Muhammad al-Tahir ibn 'Ashir, and how they treat it. The research concludes that the empowerment in Quranic perspective is a universal project aimed at controlling the life movement in order to achieve the aim of the creator in creation and the Ummah's need to rebuild the doctrinal, intellectual, and moral system to re-framing thought and behaviour, and establishing the foundations of faith and good deeds, and achieving the modern civilization. Quranic interpreters (Mufassirin) who laid down the concept for empowerment highlighted the lack of accuracy and the overall view in clarifying the reality of this concept by many interpreters.